Normative data for multiple breath washout outcomes in school-aged Caucasian children - Anagnostopoulou, Pinelopi; Latzin, Philipp; Jensen, Renee; Stahl, Mirjam; Harper, Alana; Yammine, Sophie; Usemann, Jakob; Foong, Rachel E.; Spycher, Ben; Hall, Graham L.; Singer, Florian; Stanojevic, Sanja; et al. (The European respiratory journal, 2020)
Background The nitrogen multiple breath washout (N2MBW) technique is increasingly used to assess the degree of ventilation inhomogeneity in school-aged children with lung disease. However, reference values for healthy children are currently not available. The aim of this study was to generate reference values for N2MBW outcomes in a cohort of healthy Caucasian school-aged children. - Methods N2MBW data from healthy Caucasian school-age children between 6 and 18 years were collected from four experienced centers. Measurements were performed using an ultrasonic flowmeter (Exhalyzer D, Eco Medics AG, Duernten, Switzerland) and were analyzed with commercial software (Spiroware, 3.2.1, Eco Medics AG). Normative values and upper limits of normal were generated for lung clearance index at 2.5% (LCI2.5%) and at 5% (LCI5%), moment ratios (M1/M0 and M2/M0), and a prediction equation generated for functional residual capacity (FRC). - Results Four hundred and eighty five trials from 180 healthy Caucasian children aged from 6 to 18 years were used for analysis. While LCI increased with age, this increase was negligible (0.04 units/year for LCI2.5%) and therefore fixed upper limits of normal were defined for this age group. These limits were 7.91 for LCI2.5%, 5.73 for LCI5%, 1.75 for M1/M0, and 6.15 for M2/M0 respectively. Height and weight were found to be independent predictors of FRC. - Conclusion We report reference values for N2MBW outcomes measured on a commercially available ultrasonic flowmeter device (Exhalyzer D, Eco Medics AG, Duernten, Switzerland) in healthy school-aged children to allow accurate interpretation of ventilation distribution outcomes and FRC in children with lung disease.
Gesehen am 02.04.2020